Making Accounting tutorials enjoyable - Bargate Karen (Pretoria: Unisa Press and Routledge, 2018)
This paper emanates from a case study which focussed on 15 Managerial Accounting and Financial Management (MAFM) students$1 (Benjoyment of learning MAFM in an 18-week Writing Intensive Tutorial (WIT) programme. Interactive Qualitative Analysis (IQA) was used for the research design and as a data analysis tool. Following IQA protocols participants articulate their experiences of the programme and develop emergent categories of meaning, or affinities, and the relationship between the affinities. Of the nine affinities that were confirmed as describing students$1 (Bexperiences of learning in the WIT programme, this paper reports on the students$1 (Bexperiences of one of these affinities, enjoyment. Participants said that they found the WIT programme enjoyable which made learning fun. MAFM tutorials were no longer perceived as dull and boring, but rather exciting and enjoyable. The awareness that higher education can be a fun learning environment impacted positively on students$1 (Bexperiences of learning MAFM.s
Keywords: Enjoyment; Financial management; Fun